2017
DOI: 10.1111/jwas.12478
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Two Prey Enrichment Media on Growth and Survival of Pacific Bluefin Tuna, Thunnus orientalis, Larvae

Abstract: Three experiments were conducted to investigate the growth, survival, and standardized cohort biomass of Pacific bluefin tuna, Thunnus orientalis, larvae fed nutritionally enhanced prey during the first week of feeding using two commonly used, commercially available enrichment media, AlgaMac Enrich and Marine Glos. T. orientalis larvae exhibited exponential growth in standard length and dry weight. The daily specific growth rates in length and weight are the first reported for T. orientalis larvae and the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Along with copepods, enriched rotifers have been used effectively as first feeding organisms for snapper species (Duray et al, 1996; Ibarra‐Castro et al, 2020), small mouth‐gape marine fish larvae (Alvarez‐Lajonchère et al, 1996; Geng et al, 2019; Wullur et al, 2011), and even challenging species that also exhibit rapid yolk‐sac absorption and high nutritional demand, such as scombrid larvae (Blanco et al, 2020; Kaji et al, 1999; Sawada et al, 2005; Stein et al, 2018). S‐strain rotifers are relatively easy to culture in large scale, compared to copepod species (Saillant et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Along with copepods, enriched rotifers have been used effectively as first feeding organisms for snapper species (Duray et al, 1996; Ibarra‐Castro et al, 2020), small mouth‐gape marine fish larvae (Alvarez‐Lajonchère et al, 1996; Geng et al, 2019; Wullur et al, 2011), and even challenging species that also exhibit rapid yolk‐sac absorption and high nutritional demand, such as scombrid larvae (Blanco et al, 2020; Kaji et al, 1999; Sawada et al, 2005; Stein et al, 2018). S‐strain rotifers are relatively easy to culture in large scale, compared to copepod species (Saillant et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported on the captive propagation of YFT [3][4][5], the food selectivity of larvae [6,7] age validation and growth and survival [8,9], the enzyme activities and amino acid composition of early juveniles [10], and the optimum water-quality parameters for larval growth [11]. However, high mortality at the larval and early juvenile stages was shown by Lang et al [12] and Kaji et al [13,14] for both YFT and Pacific bluefin tuna (PBT, Thunnus orientalis) [15,16].…”
Section: Introductionmentioning
confidence: 99%